Mundo metálico belenense e política cultural: declínio e reorganização do heavy metal paraense (1993-1996) - SILVA, Bernard Arthur Silva da (Universidade Federal do Pará, 2016)
This paper seeks to explain why and how the art world and Para underground circuit of Heavy Metal and the actions of its practitioners, after the 3rd Rock 24 Hours between 1993 and 1996, began to enter the transition process, accompanied by declining dispersion and sprawl, the city of Belém, resulting in the gradual decrease of events of Heavy Metal, along with elimination of the presence of metal shows at the Experimental Theatre Waldemar Henrique, Municipal Theatre of São Braz Market, Square Artist / Centur Circus and Republic Square, while setting "a modification of the city‟s metal map" by the emergence of other spaces for concerts, private spaces like Olê-Hello Park Igarapés, Nightclub Rhyno's Nightclub Spectron, Bar, Nightclub slips and Nightclub Insânu, intense stampede of practitioners of development spaces of "metal sociability", reduction in cultural news columns of the leading local newspapers (The Liberal, Diary of Para and the Province of Para), accusatory and prejudicial treatment given to the Heavy Metal and Rock in Pará relation to the 3rd Rock 24 Hours a cultural columns of some paraenses journals (The Liberal and Diary of Para), continued to launch (demo-tapes and albums in vinyl format) metal phonograph records and the gradual and permanent change in state cultural policy facing public spaces used by local Heavy Metal and Rock. Newspapers, magazines, fanzines, videos, concerts, posters, flyers, interviews and recorded such actions were used to make this discussion.